1999
DOI: 10.1149/1.1392663
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Adhesion of Diamond Films on Co Cemented Tungsten Carbide

Abstract: The extreme hardness, wear-resistance, high thermal conductivity, and low friction coefficient of diamond films, combined with the ductility and toughness of Co cemented tungsten carbide (WC-Co) allow the development of coated tools and components with new characteristics. The typical domain of diamond-coated WC-Co tools should include application to the machining of materials such as metal-matrix composite (MMC) materials, Al-Si alloys, nonferrous metals, wood, fiber-reinforced plastics, and graphite. 1-4 Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Laser treatments of WC-Co can be therefore as effective as the widely recognized Murakami's treatment insofar as the adhesion of diamond coatings on WC-Co substrates is concerned. These findings also agree with several data reported in the relevant literature, that is, that proper substrate surface roughening is a crucial issue affecting diamond film adhesion [8,34,35].…”
Section: Lasersupporting
confidence: 93%
See 1 more Smart Citation
“…Laser treatments of WC-Co can be therefore as effective as the widely recognized Murakami's treatment insofar as the adhesion of diamond coatings on WC-Co substrates is concerned. These findings also agree with several data reported in the relevant literature, that is, that proper substrate surface roughening is a crucial issue affecting diamond film adhesion [8,34,35].…”
Section: Lasersupporting
confidence: 93%
“…Average (dX/dP) −1 parameter measured on diamond deposited on laser-treated WC-Co substrate was ∼0.437 ± 0.03 kg/μm and very close to the value of 0.452 ± 0.03 kg/μm achieved on diamond deposited on MP-treated WC-Co substrate. Such results are in accordance with results measured for films of similar thickness and grown onto MP-treated WC-Co substrate [34,35]. Laser treatments of WC-Co can be therefore as effective as the widely recognized Murakami's treatment insofar as the adhesion of diamond coatings on WC-Co substrates is concerned.…”
Section: Lasersupporting
confidence: 89%
“…Although a clear correlation between diamond nucleation density and adhesive toughness has not been established yet, data from our laboratory [19] have shown that nucleation densities in the range 0.02 -0.3 Am À 2 did not significantly affect the adhesion of diamond films deposited using same CVD conditions onto WC-Co substrates previously submitted to the same pretreatment. Nevertheless, the larger nucleation densities caused by FB treatment with diamond powders allowed growing fine-grained smooth diamond films, which should allow better chip evacuation in dry cutting operations and exhibit lower friction coefficient and better wear resistance as well.…”
Section: Hfcvd Diamond Filmmentioning
confidence: 74%
“…Total chamber pressure was 18 Torr (2.4 kPa) and the gas phase was activated using a tantalum filament heated to 2350 -C. No diamond crystals nucleated at the WC-Co surface because of the low concentration of methane and the high substrate temperature [51]. However, as described in ' 2.3 and shown in Fig.…”
Section: Effect Of Substrate Pretreatmentsmentioning
confidence: 99%